2007
DOI: 10.1152/ajpendo.00119.2007
|View full text |Cite
|
Sign up to set email alerts
|

Detection of adiponectin in cerebrospinal fluid in humans

Abstract: Adiponectin circulates in the body in high concentrations, and 100-fold lower amounts were described in the cerebrospinal fluid (CSF) of mice, whereas in humans, contradictory results have been published. To clarify whether adiponectin is present in human CSF and is derived from the circulation, it was determined in human CSF and plasma of 52 nonselected patients. Adiponectin was detected by immunoblot in CSF and was quantified in CSF and serum by ELISA. CSF adiponectin was positively correlated to systemic le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
68
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 17 publications
4
68
0
Order By: Relevance
“…1H; P < 0.005). This result further confirmed that LMW adiponectin could enter the CNS from the circulation (30).…”
Section: The Trimeric Form Of Adiponectin Was Permeable To the Blood-supporting
confidence: 75%
“…1H; P < 0.005). This result further confirmed that LMW adiponectin could enter the CNS from the circulation (30).…”
Section: The Trimeric Form Of Adiponectin Was Permeable To the Blood-supporting
confidence: 75%
“…Recent studies suggest that different multimeric forms of adiponectin can influence its ability to pass the blood-brain barrier and its biological activity (14)(15)(16)(17). Next, we examined the effects of social-defeat stress on the distribution of oligomeric complexes of adiponectin using gel filtration chromatography followed by immunoblotting.…”
Section: Resultsmentioning
confidence: 99%
“…Full-length adiponectin is the predominant circulating form and can be found as a trimer, hexamer, or high molecular weight (HMW) oligomer (10,12), whereas globular adiponectin exists as a trimer (13). Evidence shows that adiponectin enters the brain from circulation (14)(15)(16)(17). Intraventricular (i.v.)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further post hoc test (Student-Newman-Keuls) indicated that the adiponectin group was significantly different from other three groups (p<0.01) tration of adiponectin also reduces serum glucose and lipid levels (Qi et al 2004). Existing data on blood brain barrier permeability to peripheral adiponectin remains equivocal, but it is clear that adiponectin is present in the brain parenchyma and cerebrospinal fluid Neumeier et al 2007;Pan and Kastin 2007).…”
Section: Discussionmentioning
confidence: 99%